2014
DOI: 10.4238/2014.august.25.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rifampicin on osteogenic differentiation and proliferation of human mesenchymal stem cells in the bone marrow

Abstract: ABSTRACT. This study was designed to investigate the effect of different concentrations of rifampicin on osteogenic differentiation and proliferation of mesenchymal stem cells (MSCs) in human bone marrow. Rifampicin treatment at 0, 4, 8, 16, 32, 64, and 128 mg/mL was applied throughout the whole process, from stromal cells purified from human bone marrow to differentiated bone cells. The effect of rifampicin on MSC proliferation was determined using the MTT assay. The effect of rifampicin on the expressions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…A number of studies have shown that the osteogenic differentiation of stem cells was inhibited to varying degrees with the increase in rifampicin concentration. [22][23][24] The present study indicated that rifapentine was related to the inhibition of osteogenic differentiation of BMSCs. HA/β-TCP is a commonly used bone graft material in clinic with good biocompatibility and bone conduction properties, 25 and previous studies have found that HA/β-TCP scaffolds can promote osteogenic differentiation of BMSCs.…”
supporting
confidence: 51%
“…A number of studies have shown that the osteogenic differentiation of stem cells was inhibited to varying degrees with the increase in rifampicin concentration. [22][23][24] The present study indicated that rifapentine was related to the inhibition of osteogenic differentiation of BMSCs. HA/β-TCP is a commonly used bone graft material in clinic with good biocompatibility and bone conduction properties, 25 and previous studies have found that HA/β-TCP scaffolds can promote osteogenic differentiation of BMSCs.…”
supporting
confidence: 51%
“…Another study demonstrated that rifampicin is cytotoxic to human bone marrow-derived MSCs at concentrations above 32 μg/mL and inhibited osteogenic diffe-rentiation potential of human bone marrow-derived MSCs in a concentration-dependent manner at concentrations ranging from 4-128 μg/mL. The collagen synthesis, mineralization effect, and expression levels of osteogenic genes in MSCs were inhibited to varying degrees with the increase in rifampicin concentration[15].…”
Section: Effects Of Various Antimicrobial Agents On Osteogenic Differmentioning
confidence: 99%
“…In these studies, rifamycin was shown to have toxic or inhibitory effects on osteoblast-like cells when used at concentrations exceeding a certain threshold. 27,28,29 While black cumin oil is well known for its various beneficial effects against several diseases 14 , its detailed effects on bone formation were examined in few studies. Wirries et al 30 reported a significant impact of TQ on proliferation, differentiation, and mineralization of cultured osteoblast cells.…”
Section: Resultsmentioning
confidence: 99%